Export promotion organizations in Latin America and the Caribbean: An institutional portrait - Jacint Jordana; Christian Volpe Martincus; Andrés Gallo (Inter-American Development Bank (IDB), 2010)
Virtually all Latin American and Caribbean countries have established specialized organizations to promote their exports. Existing analyses of these organizations are at best partial and fragmentary. This paper aims at overcoming these limitations of the literature by presenting a consistent, detailed organizational characterization of the major export promotion entities in their respective countries. This characterization is primarily based on data collected through an extensive survey that we have conducted among organizations in the region, and, to put them into an appropriate perspective, among relevant organizations from countries outside of the region. Moreover, for a few countries, we have carried out in-depth case studies not only to report more precise information on those aspects covered by the survey, such as the number and diversity of other actors, both public and private, engaged in export promotion along with their interaction patterns, but also to examine additional factors that are likely to be helpful in understanding the current organizational configuration of the aforementioned entities and their potential effectiveness, such as the historical institutional process leading to their creation.
hdl:11319/3183
Keywords: F13; F14; O24; O54; 330; Export Promotion Organizations; Models; Latin America